2019
DOI: 10.1002/ange.201911995
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating the Electrocatalytic CO2 Reduction Reaction over a Model Single‐Atom Nickel Catalyst

Abstract: Designing effective electrocatalysts for the carbon dioxide reduction reaction (CO2RR) is an appealing approach to tackling the challenges posed by rising CO2 levels and realizing a closed carbon cycle. However, fundamental understanding of the complicated CO2RR mechanism in CO2 electrocatalysis is still lacking because model systems are limited. We have designed a model nickel single‐atom catalyst (Ni SAC) with a uniform structure and well‐defined Ni‐N4 moiety on a conductive carbon support with which to expl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 58 publications
4
30
0
Order By: Relevance
“…Recently, Gu et al 52 observed that the initial electron for reduction of CO 2 is decoupled from a proton transfer on Fe 3+ -N-C and found that CO 2 adsorption is fast, and the rate limiting step is protonation of the adsorbed CO 2to form an adsorbed COOH intermediate, with an experimental Tafel slope of 64 mV dec −1 . Moreover, experiments by Liu et al 29 for CO 2 RR on a Ni-single atom catalyst confirmed the presence of Ni + by operando spectroscopic characterization. They observed that the proton transfer to the adsorbed *CO 2 is the rate determining step with a Tafel slope of 72 mV dec −1 .…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Recently, Gu et al 52 observed that the initial electron for reduction of CO 2 is decoupled from a proton transfer on Fe 3+ -N-C and found that CO 2 adsorption is fast, and the rate limiting step is protonation of the adsorbed CO 2to form an adsorbed COOH intermediate, with an experimental Tafel slope of 64 mV dec −1 . Moreover, experiments by Liu et al 29 for CO 2 RR on a Ni-single atom catalyst confirmed the presence of Ni + by operando spectroscopic characterization. They observed that the proton transfer to the adsorbed *CO 2 is the rate determining step with a Tafel slope of 72 mV dec −1 .…”
Section: Discussionmentioning
confidence: 74%
“…It has large surface area, high conductivity, high stability, and the capability to tune electronic properties by forming strong chemical bonds to guest atoms [22][23][24] . Several experimental studies have been published recently on the CO 2 reduction reaction (CO 2 RR) for the nickel single atom catalysts (Ni-SACs) on graphene 20,21,[25][26][27][28][29] , but the performance varies markedly perhaps because of differences in the number of carbon or nitrogen bonds to Ni.…”
mentioning
confidence: 99%
“…2G). Results from the aberration-corrected HAADF-STEM and x-ray absorption spectroscopy (XAS) measurements clearly confirm the well-defined Ni-N 4 moiety on carbon support (66).…”
Section: Molecular Bridgingmentioning
confidence: 70%
“…In the work conducted by Liu and colleagues, atomically dispersed Ni(I) has been proven as the active site for CO 2 RR (55); the asdeveloped single-Ni atom catalyst exhibits high intrinsic activity for CO 2 reduction, reaching a TOF of 14,800 hours −1 with 97% Faradaic efficiency at a mild overpotential of 0.61 V. The following research from the same group further identified the high activity of Ni + in a model Ni-based SAC for CO 2 activation through operando XAS and Raman measurements (Fig. 6C) (66).…”
Section: Co 2 Reduction Reactionmentioning
confidence: 92%
See 1 more Smart Citation